The effect of endurance and endurance-strength training on body composition and cardiometabolic markers in abdominally obese women: a randomised trial - Jamka, Małgorzata; Mądry, Edyta; Krzyżanowska-Jankowska, Patrycja; Skrypnik, Damian; Szulińska, Monika; Mądry, Radosław; Lisowska, Aleksandra; Batyrova, Gulnara; Duś-Żuchowska, Monika; Gotz-Więckowska, Anna; Bogdański, Paweł; Walkowiak, Jarosław (Scientific reports, 2021)
Studies comparing the effect of endurance and endurance-strength training on cardiometabolic markers provided inconsistent results. Therefore, the study aimed to compare the effect of endurance and endurance-strength training on body composition and cardiometabolic parameters in abdominally obese women. In this randomised trial, 101 subjects were included and divided into endurance (n = 52) and endurance-strength (n = 49) training. During the 12-week intervention, participants performed supervised one-hour training three times a week. Body composition, blood pressure (BP), markers of glucose and lipid homeostasis, and myoglobin levels were measured before and after the intervention. In total, 85 subjects completed the trial. Both interventions decreased fat mass and visceral adipose tissue and increased free fat mass, appendicular lean mass index and lean mass index. Neither endurance training nor endurance-strength training affected glucose and lipid metabolism. However, only endurance training significantly decreased paraoxonase and myoglobin levels. Both training programmes significantly decreased BP, with a more reduction of diastolic BP noted in the endurance group. In conclusion, both training programmes had a favourable effect on body composition but did not improve glucose and lipid homeostasis. Besides, endurance training decreased paraoxonase activity and myoglobin levels and was more effective in reducing BP. The study was registered with the German Clinical Trials Register (DRKS) within the number: DRKS00019832 (retrospective registration), date of registration: 26/02/2020.